Analisis Kinerja Sistem Penilaian Lomba Tari Bali Berbasis Mobile - I Kadek Dwi Gandika Supartha; I Putu Agus Sukanta Wijaya (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Balinese dance is a type of dance originating from Bali that has existed for a long time and has been passed down from generation to generation by Balinese people. Balinese dance has 3 kinds of categories, namely Wali Dance (sacred), Bebali Dance and Balih-Balihan Dance (Profane). Balinese dances that are sacred are usually performed on certain days or during religious ceremonies, while profane dances are usually performed for entertainment. In Bali, many types of Balinese dances are contested, such as Barong Dance, Jauk Manis Dance, Jauk Keras Dance, Baris Dance and so on. In this study, the design and development of a Balinese dance competition assessment application was carried out which aims to facilitate the performance of the competition organizing committee and the judges during the assessment and recording of the participants' scores after the competition is held and can display the values transparently to the public. Tests show that when the application is run, it gets a value of 312.3999996185303 on the application and a value of 312.4 in the manual assessment process. The dance assessment application and manual assessment have almost the same value with a percentage accuracy of 99.9%.